Microscopic multifrequency magnetic resonance elastography of ex vivo abdominal aortic aneurysms for extracellular matrix imaging in a mouse model - Mangarova, Dilyana B.; Bertalan, Gergely; Jordan, Jakob; Brangsch, Julia; Kader, Avan; Moeckel, Jana; Adams, Lisa C.; Sack, Ingolf; Taupitz, Matthias; Hamm, Bernd; Braun, Juergen; Makowski, Marcus R. (Acta Biomaterialia, 2022)
An abdominal aortic aneurysm (AAA) is a permanent dilatation of the abdominal aorta, usually accompanied by thrombus formation. The current clinical imaging modalities cannot reliably visualize the thrombus composition. Remodeling of the extracellular matrix (ECM) during AAA development leads to stiffness changes, providing a potential imaging marker. 14 apolipoprotein E-deficient mice underwent surgery for angiotensin II-loaded osmotic minipump implantation. 4 weeks post-op, 5 animals developed an AAA. The aneurysm was imaged ex vivo by microscopic multifrequency magnetic resonance elastography (µMMRE) with an in-plane resolution of 40 microns. Experiments were performed on a 7-Tesla preclinical magnetic resonance imaging scanner with drive frequencies between 1000 Hz and 1400 Hz. Shear wave speed (SWS) maps indicating stiffness were computed based on tomoelastography multifrequency inversion. As control, the aortas of 5 C57BL/6J mice were examined with the same imaging protocol. The regional variation of SWS in the thrombus ranging from 0.44 ± 0.07 to 1.20 ± 0.31 m/s was correlated fairly strong with regional histology-quantified ECM accumulation (R2 = 0.79). Our results suggest that stiffness changes in aneurysmal thrombus reflect ECM remodeling, which is critical for AAA risk assessment. In the future, µMMRE could be used for a mechanics-based clinical characterization of AAAs in patients. Statement of significance: To our knowledge, this is the first study mapping the stiffness of abdominal aortic aneurysms with microscopic resolution of 40 µm. Our work revealed that stiffness critically changes due to extracellular matrix (ECM) remodeling in the aneurysmal thrombus. We were able to image various levels of ECM remodeling in the aneurysm reflected in distinct shear wave speed patterns with a strong correlation to regional histology-quantified ECM accumulation. The generated results are significant for the application of microscopic multifrequency magnetic resonance elastography for quantification of pathological remodeling of the ECM and may be of great interest for detailed characterization of AAAs in patients.
CRIS-Team Scopus Importer:2022-08-03
Keywords: AAA; Magnetic resonance elastography; Proof-of-concept; Stiffness